Factors associated with death and readmission into the Intensive Care Unit Factores asociados a la muerte y a la readmisión en Unidad de Terapia Intensiva Fatores associados ao óbito e a readmissão em Unidade de Terapia Intensiva - Maria Claudia Moreira da Silva; Regina Marcia Cardoso de Sousa; Katia Grillo Padilha (Universidade de São Paulo, 2011)
This study identifies the factors associated with death and readmission into the Intensive Care Unit. This is a longitudinal prospective study of 600 adult patients admitted in general Intensive Care Units of four hospitals in São Paulo, Brazil. The multiple regression analysis showed that patients with a longer length of stay and higher Nursing Activities Score, Simplified Acute Physiology Score II and Logistic Organ Dysfunction Score on the last day in the unit had a higher chance of death. Nevertheless, higher Nursing Activities Score and Logistic Organ Dysfunction Score on the first day in the intensive care unit were protective factors against death. Viral hepatitis as an antecedent increased the chance of readmission. On the other hand, higher Nursing Activities Score at discharge decreased this risk. It was concluded that the nursing workload was the main variable related to the outcomes analyzed. El objetivo de este estudio fue identificar los factores asociados con muerte y readmisión de pacientes en Unidad de Terapia Intensiva. Se trata de un estudio prospectivo longitudinal con 600 pacientes adultos, internados en Unidades de Terapia Intensiva general de cuatro hospitales del Municipio de Sao Paulo. El análisis de regresión múltiple mostró que los pacientes con mayor tiempo de internación, que tuvieron puntajes más elevados en: Nursing Activities Score, Simplified Acute Physiology Score II y Logistic Organ Dysfunction Score, en el último día de internación, tuvieron más probabilidad de morir; por otro lado las puntuaciones más altas del Nursing Activities Score y Logistic Organ Dysfunction Score, en la admisión, fueron factores protectores para muerte en la unidad. El antecedente de hepatitis viral aumentó la probabilidad de readmisión; al contrario, la mayor puntuación del Nursing Activities Score en el alta disminuyó ese riesgo. Se concluyó que la carga de trabajo de enfermería fue una variable destacada en relación a los resultados analizados. O objetivo deste estudo foi identificar os fatores associados ao óbito e à readmissão dos pacientes em unidade de terapia intensiva. Estudo prospectivo longitudinal, com 600 pacientes adultos, internados em unidade de terapia intensiva geral de quatro hospitais do município de São Paulo. A análise de regressão múltipla mostrou que os pacientes com maior tempo de internação, Nursing Activities Score, Simplified Acute Physiology Score II e Logistic Organ Dysfunction Score mais elevados, no último dia de internação, tiveram mais chance de morrer, porém, as pontuações mais altas do Nursing Activities Score e Logistic Organ Dysfunction Score, na admissão, foram fatores protetores para óbito na unidade. Antecedente de hepatite viral aumentou a chance de readmissão; ao contrário, a maior pontuação do Nursing Activities Score, na alta, diminuiu esse risco. Concluiu-se que a carga de trabalho de enfermagem foi variável de destaque em relação aos desfechos analisados.